2014
DOI: 10.1037/lhb0000059
|View full text |Cite
|
Sign up to set email alerts
|

The role and reliability of the Psychopathy Checklist—Revised in U.S. sexually violent predator evaluations: A case law survey.

Abstract: The civil commitment of offenders as sexually violent predators (SVPs) is a highly contentious area of U.S. mental health law. The Psychopathy Checklist-Revised (PCL-R) is frequently used in mental health evaluations in these cases to aid legal decision making. Although generally perceived to be a useful assessment tool in applied settings, recent research has raised questions about the reliability of PCL-R scores in SVP cases. In this report, we review the use of the PCL-R in SVP trials identified as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 40 publications
7
62
3
Order By: Relevance
“…We could not calculate inter-rater reliability statistics because the evaluations in this sample were completed by individual evaluators. It would have been ideal to be able to calculate inter-rater reliabilities to compare to other recent field research that has suggested poor inter-rater reliability of risk assessment tools (particularly the PCL-R) in clinical settings (e.g., Boccaccini, Turner, & Murrie, 2008;DeMatteo, et al, 2014;Edens, Boccaccini, & Johnson, 2010). Given those recent findings, there is reason to be concerned about the inter-rater reliability between clinicians in the present sample.…”
Section: Research Versus Field Studiesmentioning
confidence: 95%
“…We could not calculate inter-rater reliability statistics because the evaluations in this sample were completed by individual evaluators. It would have been ideal to be able to calculate inter-rater reliabilities to compare to other recent field research that has suggested poor inter-rater reliability of risk assessment tools (particularly the PCL-R) in clinical settings (e.g., Boccaccini, Turner, & Murrie, 2008;DeMatteo, et al, 2014;Edens, Boccaccini, & Johnson, 2010). Given those recent findings, there is reason to be concerned about the inter-rater reliability between clinicians in the present sample.…”
Section: Research Versus Field Studiesmentioning
confidence: 95%
“…(e.g., DeMatteo, et al, 2014;Murrie et al, 2008;Murrie, Boccaccini, Turner, Meeks, Woods, & Tussey, 2009) and in Canada (Lloyd, Clark, & Forth, 2010). Beyond these studies, surveys of judges and attorneys consistently reveal their concern about bias among experts as well (e.g., Krafka, Dunn, Johnson, Cecil, & Miletich, 2002;Shuman, Whitaker, & Champagne, 1994).…”
Section: Bias In Forensic Evaluationsmentioning
confidence: 98%
“…The forensic identification finding by mental health professionals in adversarial forensic settings has been observed by other investigators as well, including in several recent field studies -despite the ethical guidelines about striving to be unbiased and impartial (e.g., DeMatteo, Edens, Galloway, Cox, Toney Smith, & Formon, 2014;Lloyd, Clark, & Forth, 2010;Murrie, Boccaccini, Johnson, & Janke, 2008;Murrie, Boccaccini, Turner, Meeks, Woods, & Tussey, 2009;Otto, 1989). …”
Section: Forensic Identification (Aka Adversarial Allegiance) and mentioning
confidence: 99%